Parallel numerical computations with applications - Yang, Tianruo (The Kluwer international series in engineering and computer science ;, 1999)
"Parallel Numerical Computation with Applications contains selected edited papers presented at the 1998 Frontiers of Parallel Numerical Computations and Applications Workshop, along with invited papers from leading researchers around the world."--BOOK JACKET. "This state-of-the-art volume will be an up-to-date resource for researchers in the areas of parallel and distributed computing."--BOOK JACKET.